IT governance for public universities: developing a model - Bianchi, Isaías Scalabrin (2015)
Information technology (IT) has become essential in supporting the growth and sustainability of all types of organizations. Universities are one of those types that are more and more dependent on IT having a technological infrastructure made of heterogeneous technologies that turns IT Governance into a real challenge. The teaching-learning and research processes, nuclear for universities, require effective and efficient IT governance so universities remain competitive. IT governance calls for the definition and implementation of formal practices at the highest level in the organization involving structures, processes and relational mechanisms for the creation of business value from IT investments. However, it is quite notorious the difficulty in defining and implementing those practices from frameworks such as COBIT, ITIL, ISO/IEC 38500, among others. The level of adoption of such frameworks at universities is quite low, superficial or limited in scope. To address these issues, we propose, using design science research, the development of an IT governance model for public universities. The model will be designed having the appropriate mechanisms identified through survey research and case studies involving Portuguese and Brazilian public universities. We expect to contribute with a model having structures, processes and relational mechanisms suitable for the public sector universities with the guidelines for effective and efficient IT governance. Moreover, contributions to the body of knowledge, regarding the adoption of frameworks such as COBIT and ITIL, taking in consideration contextual and contingency factors, are also expected in what particularly relates to Portuguese and Brazilian public universities.